(untitled) (Hungarian Journal of Industry and Chemistry, 2010)
The aim of this work was to give a general overview on the type and behaviour of anaerobic membrane bioreactors, which are intensively studied for waste water treatment processes. The role of the membrane, the possible design, structures of the bioreactors, the effect of environment are presented here.